The management of enterprises and a new perspective of the personnel function - Florjancic, Joze (Marketing & Menedzsment, 2019)
Members of personnel staff of companies are facing a great challenge now. Extensive changes we are witnessing nowadays - both economical and political - are either stipulating or paving the way for completely different business conditions we have been used to so far. A great number of new companies have emerged and, on the other hand, the existing companies are faced w ith redundancy labor force. Some other firms have troubles, go bankrupt, etc. New firms, as a rule, are lacking experience o f the personnel management, while the existing companies are arguing that, in most cases, they have no further use for their previous experience since the expectations with regard to personnel services have changed entirely.